Process Automation with BPM and Emerging Technologies for Service and Industrial Process Optimization: Systematic Mapping - Oliveira, Alisson; Silva, Alyne; Camara, Davi; Silva, Eduardo; Santiago, Lindalva (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI), 2025)
Context: The adoption of emerging technologies such as Artificial Intelligence (AI), Machine Learning (ML), Robotic Process Automation (RPA), and Process Mining (PM) is transforming business process management (BPM) and mainly its automation process, enhancing operational efficiency in services and industrial processes, and promoting innovation. Problem: The integration of emerging technologies with BPM faces organizational and technical challenges, including workforce adaptation, resistance to change and high costs, limiting its potential to increase efficiency and productivity. Solution: This article aims to investigate and analyze the approaches and structures that enable the integration of emerging technologies with BPM, addressing key questions of interest regarding their impact, implementation, and effectiveness in organizational settings. Information Systems Theory: This research was based on the aegis of the Diffusion of Innovations Theory, exploring how emerging technologies drive innovations in BPM, transforming organizational processes, accelerating automation and promoting operational efficiency and workforce reorganization. Method: We conducted a systematic mapping of studies published between 2019 and 2024, with a quantitative analysis of the selected studies. Summary of Results: The analysis highlighted AI, RPA, and Process Mining as the most cited technologies in BPM automation. However, gaps were identified in the integration of emerging technologies, pointing out technical challenges and opportunities for improvement. Contributions and Impact: This article provides insights into the integration of emerging technologies with BPM, addressing workforce adaptation and resistance to change. Its findings foster artifacts for IT managers and BPM professionals, promoting efficiency, competitiveness, innovation and new academic research.